Menstrual hygiene management practice and associated factors among secondary school girls in finot selam town, northwest Ethiopia, 2019 - Zinie Abita; Rahma Ali; Bitiya Admassu (International Journal of Sexual and Reproductive Health Care - Peertechz Publications, 2021)
Background: Menstrual hygiene is vital to the health, well-being, dignity and productivity of women and girls. However, there is a problem on menstrual hygiene management especially among communities in which discussing about menstrual hygiene is taboo in their culture.  Objective: The study was aimed to assess menstrual hygiene management practice and associated factors among secondary school girls in Finot Selam town, Ethiopia 2019. Method: A cross-sectional study was conducted among randomly selected school girls in Finot Selam town from March 20 to 30, 2019. Descriptive summary was done as a mean, frequency and proportion. In bivariate analysis variables with a p-value<0.25 were candidate for multivariable logistic regression and those with a p-value<0.05 in multivariable analysis were considered as having statistically significant association with menstrual hygiene practice. Thematic analysis was employed for the qualitative data.  Result: A total of 442 school girls were participated in the study, with response rate of 99.1%. About 68 % of adolescent girls had good practice of menstrual hygiene management. The odd of good practice was 3.4 times higher [AOR=3.40; 95% C.I: (1.16, 9.97)] among girls whose fathers' education was colleges and above compared to those whose father was illiterate. Information before menarche [AOR=3.95; 95% C.I: (2.13, 7.33)], discussion about menstrual hygiene with their parents [AOR =2.75; 95% CI: (1.71, 4.43) and knowledge on sanitary pads in the market [AOR=2.10; 95% CI: (1.18, 3.28)] were the other factors associated with menstrual hygiene management. Findings from in-depth interview found that inadequate sanitation facility was reported as a problem for girls to manage their menstrual hygiene in school. Conclusion: Most of girls in this study have good practice of menstrual hygiene management. Paternal education, discussion with parents about menstruation, knowledge on sanitary pads and prior information were the factors associated with the practice of menstrual hygienic management.